Studi Kasus Edukasi Digital Deteksi Dini Stroke Pada Penderita Hipertensi - Asri; Hakim, Muhammad Nidhom (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Hypertension is a trigger factor for stroke, research shows that people with hypertension end up having a stroke. Cultivating self-awareness is very important in preventing complications from an illness. Lack of knowledge and ability to identify signs and symptoms of stroke early is the cause of delays in treatment during the golden period (Galvani et al, 2022).Objective: To identify the level of knowledge before and after education on early stroke detection in hypertension sufferers.Method: using descriptive with a case study approach. This research was carried out in several stages, namely: identifying before providing health education, providing health education, identifying after providing health education using video media to patients with the aim of increasing knowledge in an effort to detect early stroke.Results: 40% of them had knowledge that could be categorized as “Fair”, while 60% had knowledge that could be categorized as “Good”.